Ecolinguistics analysis of environmental content in English and German language textbooks - Wening Sahayu; Sulis Triyono; Sahnaz Natasya Fath (Universitas Syiah Kuala, 2025)
Extensive research has been conducted on environmental integration within textbooks linguistically, visually, or statistically. However, comparative analysis involving examining multiple language textbooks has been relatively underutilized in the existing body of research. This study seeks to address this gap by employing a comparative approach to evaluate environmental discourse in two foreign language textbooks, Bahasa Inggris (English) and Kontakte Deutsch 3 (German). Using Eco-Critical Discourse Analysis (ECDA), this research uncovered the ecological integration and ideological underpinnings present in each textbook. The analysis indicates that Bahasa Inggris contains 87% eco-beneficial discourse, with 8% eco-ambivalent and 6% eco-destructive content, suggesting a solid emphasis on positive environmental messaging. In contrast, Kontakte Deutsch 3 exhibits 95% eco-beneficial discourse, no eco-ambivalent content, and only 5% eco-destructive discourse, reflecting a clearer commitment to positive ecological messaging. Further, Kontakte Deutsch 3 emphasizes ecological sensitivity (97%) more than Bahasa Inggris (73%). However, Bahasa Inggris offers more content on ecological knowledge (15%) and skills (13%) compared to Kontakte Deutsch 3 (1.5% each). Both types minimally address ecological distribution, Bahasa Inggris, including original representation (0.6%), and Kontakte Deutsch 3 neglect it. Overall, Kontakte Deutsch 3 presents a more pronounced focus on positive environmental content and emotional awareness, while Bahasa Inggris provides broader ecological knowledge and practical skills.